Value of Comparative-dialectological Competence in the Future Russian Language Teachers Professional Development - Nosirovna, Musurmankulova Madina (International Journal of Psychosocial Rehabilitation, 2020)
This article discusses the importance of dialect concepts in a comparative plan and the path of development of future teachers in the professional sphere. In long-distance areas dialects, dialect systems and folklore still exist. Improving the system of comparative dialect competence of the Russian and Uzbek languages at present can give a methodical direction to students of the national group. A competent approach to the study of the dialect system develops the knowledge of future Russian language teachers in national schools. Dialect words in both the Uzbek language and the Russian language are considered in a semantic aspect.